Modeling the metabolic response of A2780 ovarian cancer cells to gold-based cytotoxic drugs - Walter Vieri; Veronica Ghini; Paola Turano; Lara Massai; Luigi Messori; Marco Fondi (npj Systems Biology and Applications)
Abstract Gold compounds are a promising class of experimental anticancer metallodrugs. Unlike platinum-based drugs, their antiproliferative effects are thought to result mainly from modulation of cancer cell metabolism rather than direct interaction with DNA. Previous NMR studies have shown that four cytotoxic gold compounds - auranofin, aurothiomalate and two gold N-heterocyclic carbenes - induce distinct metabolic changes in A2780 ovarian cancer cells, suggesting the occurrence of different mechanisms of action. To better understand these effects, we constructed a genome-scale metabolic model (GEM) of A2780 cells to analyze the NMR-detected metabolomic changes. The model successfully predicts the diverse metabolic responses induced by each gold compound and identifies common metabolic changes. These results confirm the potential of GEMs as a powerful tool for interpreting and predicting cellular responses to gold-based drugs, providing insights into their mechanisms of action and potential therapeutic applications.